The relation of complex problem solving with reflective abstraction: a systematic literature review - Nuhyal Ulia; Stevanus Budi Waluya; Isti Hidayah; Emi Pujiastuti (Institute of Advanced Engineering and Science, 2024)
Complex problem solving (CPS) is a new paradigm in solving problems and is one of the soft skills needed to face the industrial revolution 4.0. Reflective abstraction is associating and modifying pre-existing conceptions into new situations. This article reviews research on CPS and reflective abstraction. This research is needed to know the relationship between reflective abstraction and CPS. The systematic writing of this review was assisted by the Publish or Perish 7 application, Mendeley, and VOSviewer. A literature search was performed through the ScienceDirect and ERIC databases. Based on the search results with the term “complex problem solving” and several exclusion criteria, 58 articles were found, whereas with the word “reflective abstraction” there were 23 articles, totaling 81 papers. Based on the literature review, it was found that there is a relationship between CPS and reflective abstraction by obtaining common ground in the form of prior knowledge. CPS requires prior knowledge from reflective abstraction to integrate the most relevant information. To improve CPS, efforts and special attention can be made to build initial knowledge through reflective abstraction. This article contributes to further research and becomes a study for the themes of CPS and reflective abstraction in learning and education.